Polyphosphate kinase is essential for biofilm development, quorum sensing, and virulence of Pseudomonas aeruginosa - Rashid, M. Harunur (The National Academy of Sciences, 2000)
The human opportunistic pathogen Pseudomonas aeruginosa causes a variety of infections in immunocompromised hosts and in individuals with cystic fibrosis. A knockout mutation in the polyphosphate kinase (ppk) gene, encoding PPK responsible for the synthesis of inorganic polyphosphate from ATP, renders P. aeruginosa cells unable to form a thick and differentiated biofilm. The mutant is aberrant in quorum sensing and responses in that production of the quorum-sensing controlled virulence factors elastase and rhamnolipid are severely reduced. In a burned-mouse pathogenesis model, the virulence of the mutant is greatly reduced with severe defects in the colonization of mouse tissues. The conservation of PPK among many bacterial pathogens and its absence in eukaryotes suggest that PPK might be an attractive target for antimicrobial drugs.